Pathogenic Shiga toxin-producing Escherichia coli in the intestine of calves - Sandhu, K. S. (2002)
The purpose of this study was to compare the pathological effects of Shiga toxin-producing Escherichia coli (STEC) that vary in their association with bovine and human disease. Shiga toxin-producing E. coli of serotypes associated with both dysentery in calves and hemolytic uremic syndrome (HUS) in humans (O5:H-, O26:H11, O111:H-, O113:H21) were compared with O157:H7 STEC, which are associated with HUS in humans but not with disease in calves. The STEC were administered orally to 80 day-old chicks and into ligated loops in the ileum and colon of four 2- to 6-day-old calves. Examination of the ceca of the chickens 10 d postchallenge showed no adherence or tissue abnormality for any isolate. The calves were euthanized 8 to 10 h postinoculation, and sections of the intestinal loops were examined by light microscopy, transmission and scanning electron microscopy, and immunohistochemistry. All strains showed consistent focal adherence associated with mild lesions in the colon. Attaching and effacing lesions were observed with the eae-positive strains. Ileal lesions were similar to the colonic ones but were sometimes severe, with marked polymorphonuclear leukocyte proliferation in the lamina propria. It is concluded that chickens were unsuitable for studying interaction of STEC with the intestine and that there was no difference in the interaction of the ligated calf intestine with STEC of serotypes associated with disease in calves compared with O157:H7 STEC.